Analisis Desain Formulir Rawat Jalan di Rumah Sakit - Poernareksa, Dwidya; Qomah, Isti; Sania, Yasmine; Azharani, Nisfiya (HB PRESS, 2024)
According to the Regulation of the Minister of Health of the Republic of Indonesia Number 269 of 2008 concerning Medical Records, Article 3 Paragraph (2), medical records must include the patient's identity, date and time, and anamnesis results, which should at least include complaints and medical history. Medical records are documented in specially named forms to prevent loss or duplication. Aspects to consider when designing a form include anatomical, physical, and content aspects. This study aims to describe the outpatient electronic medical record form based on these three aspects in hospitals. The research subjects were 1 medical records officer and 1 head of the medical records department. Observations and interviews revealed no issues with filling out or anatomical aspects of the outpatient form. The physical aspects of the form were complete, but there were problems with printing; the paper used was below the 80-gram standard, making it prone to damage and tearing over time, which affects print or writing quality. The content aspects of the electronic outpatient form were appropriate, though issues arose when officers or doctors forgot to enter the date, impacting the completeness of the form.